Pradators - Stoneshouse, Bernard; Nang Chan Yeema (New York, USA Tangerine Press, 1999)
An introduction to predators on land, in the air, and in the water, highlighting the amazing range of adaptation employed to catch, subdue, and consume a living meal.
Keywords: Juvenile Nonfiction